2022
DOI: 10.3390/jcm12010014
|View full text |Cite
|
Sign up to set email alerts
|

Non-Adherence to Anti-Osteoporosis Medication: Factors Influencing and Strategies to Overcome It. A Narrative Review

Abstract: To evaluate the reasons for inadequate adherence to osteoporosis therapy and to describe the strategies for improving adherence to and persistence with regular medications, we conducted a review of the literature. The primary outcome of the study was the determination of the factors adverse to the onset and maintenance of anti-osteoporosis therapies. Secondly, we focused on studies whose efforts led to finding different strategies to improve adherence and persistence. We identified a total of 26 articles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Our research also revealed that exercise and anti-osteoporosis were effective strategies for preventing refractures. Exercise improves bone strength to provide effective biomechanical factors for promoting bone growth [32], and drug therapy enhances the biological environment of bone metabolism to improve bone quality [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research also revealed that exercise and anti-osteoporosis were effective strategies for preventing refractures. Exercise improves bone strength to provide effective biomechanical factors for promoting bone growth [32], and drug therapy enhances the biological environment of bone metabolism to improve bone quality [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies [34][35][36] show that patients exhibit poor adherence to anti-osteoporosis medications and regular physical activity. The primary condition of the patient should be taken into consideration when choosing anti-osteoporosis drugs and complete health counseling, and a dynamic therapeutic management plan with long-term follow-up is also indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is one of the most common diseases of our times, affecting more than 200 million people worldwide, and represents a major public health problem, considering that one of the main complications of this disease is fragility fractures, which in turn carry a high social and economic cost [ 52 ]. Although multiple pharmacological therapies are available to treat the various stages of this pathology, many patients at risk or already suffering from the disease do not start or do not scrupulously follow the prescribed protocols [ 52 ]. The association between osteoporosis and the risk of PJI has not yet been extensively investigated in the literature.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Preventive measures can be taken to reduce the occurrence of osteoporotic fractures by identifying high-risk groups early on and initiating appropriate treatment [ 6 9 ]. Safe and effective medications are available to reduce the risk of fractures [ 10 ].…”
Section: Introductionmentioning
confidence: 99%